VALUATION OF DIGITAL START-UP BUSINESS : A CASE STUDY FROM DIGITAL PAYMENT SOLUTION SERVICES COMPANY - Aulia Dwi Ikhwan; Raden Aswin Rahadi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Despite its promising, innovative and fast growth in the last several years, startup business is a high risk enterprise with potential high return on investment. Funding investment plays critical role in this issue in terms of supporting the development of startup business. A startup's ability to acquire financing at the right time is critical to its long-term success. Therefore, business valuation is become critical and essential for startup business as the fundamental step of funding process. Based on this notion, PT. AXY is willing to determine their value in order to manage investment opportunity ahead. Estimating value of PT. AXY’s business is referring to its strategic plan since investment will be support to expand team and realizing projects. The strategic plan is divided into three scenario which are optimist, base, and pessimist. By using First Chicago Method (FCM) and Venture Capital Method (VCM) as two among several methods which considered suitable with PT.AXY’s current condition. After compiling those three scenario using weighted sum, the results of valuation using FCM is IDR 556,550,469,235 and using VCM is IDR 506,381,073,478. Finally by using pareto optimality, we determine that overall valuation of PT.AXY is IDR 546,516,590,084. Sensitivity Analysis also used to determine which factors that directly impact to the valuation. By assessing several parameters that change for each variable to be swinged +/- 20%, as result revenue growth, discount rate and salary expense are parameters that considered as sensitive that management could pay attention to since it will be directly affect to the company’s valuation.